Improving the reading and writing skills of grade 1 students at Malaysia - Darliana Sormin; Mira Rahmayanti Sormin; Masdelima Azizah; Jumaita Nopriani Lubis; Adek Kholijah (Universitas Muhammadiyah Malang, 2025)
The ability to read and write in grade 1 elementary school students is often a challenge in early education, with traditional teaching methods sometimes being less effective in improving these basic skills. This research aims to evaluate the effectiveness of Problem Based Learning (PBL) in improving the reading and writing skills of grade 1 elementary school students at ICC Al-Anshar Bahau. Using a one group pretest-posttest design, this research involved six students with skills assessment through pretest and posttest. The results of the analysis showed significant improvements in reading and writing skills, with the average student score increasing from 10.8 points on the pretest to 18 points on the posttest. These findings indicate that PBL can effectively improve reading and writing skills in grade 1 elementary school students. The implication of this research is that implementing PBL can be a useful strategy in basic education curricula, with the potential to improve overall student engagement and learning outcomes. This study suggests further research with a more comprehensive design and larger sample size to confirm the results and expand understanding of the effectiveness of PBL in a broader context.